2014
DOI: 10.1111/liv.12558
|View full text |Cite
|
Sign up to set email alerts
|

The organic solute transporters alpha and beta are induced by hypoxia in human hepatocytes

Abstract: Background & AimsThe organic solute transporters alpha and beta (OSTα-OSTβ) form a heterodimeric transporter located at the basolateral membrane of intestinal epithelial cells and hepatocytes. Liver injury caused by ischaemia-reperfusion, cancer, inflammation or cholestasis can induce a state of hypoxia in hepatocytes. Here, we studied the effect of hypoxia on the expression of OSTα-OSTβ.MethodsOSTα-OSTβ expression was measured in Huh7 cells and primary human hepatocytes (PHH) exposed to chenodeoxycholic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…The similar changes in nonsepsis patients may be explained by ischemia/reperfusion‐related inflammation and cytokine release, because a large proportion of nonsepsis patients were admitted to the ICU postcardiac surgery. These findings also are consistent with hypoxia‐associated increases in hepatic basolateral organic anion transporter α and β (OSTα/β) expression, which may contribute to increased efflux of bile acids from hepatocytes into the systemic circulation …”
Section: Transporter Changes Associated With Acute Disease and Alteresupporting
confidence: 70%
“…The similar changes in nonsepsis patients may be explained by ischemia/reperfusion‐related inflammation and cytokine release, because a large proportion of nonsepsis patients were admitted to the ICU postcardiac surgery. These findings also are consistent with hypoxia‐associated increases in hepatic basolateral organic anion transporter α and β (OSTα/β) expression, which may contribute to increased efflux of bile acids from hepatocytes into the systemic circulation …”
Section: Transporter Changes Associated With Acute Disease and Alteresupporting
confidence: 70%
“…The recent discovery that bile acid concentrations are increased in the serum and liver of patients with NASH (22,37) supports the finding that OST␣/␤ is induced in patients with NASH. In vitro data also support this hypothesis, because both hypoxia and elevated bile acid concentrations, conditions similar to patients with NASH (37,46), induced OST␣ and OST␤ expression (52). OST␣/␤ induction is mediated through the bile acid-activated farnesoid X receptor (FXR, NR1H4) pathway (7,65).…”
Section: Introductionmentioning
confidence: 77%
“…have also demonstrated that no difference in mRNA of CAT‐2 occurs after kidney I/R; on the contrary, a decrease, although not significant, in mRNA CAT‐2A was found . The role of I/R injury in the regulation of hepatic transporters is not new in the literature, though not sufficiently explored: a previous study has demonstrated that hypoxia regulates the expression of hepatobiliary transporter genes ; further data in human hepatocytes have demonstrated that the organic solute transporters alpha and beta are induced by hypoxia .…”
Section: Discussionmentioning
confidence: 97%